Real and imagined readers: censorship, publishing and reading under apartheid - Matteau, Rachel (My University, 2012)
This thesis studies the readership of literature that was banned under the various laws that comprised the censorship system, focusing on the apartheid period, from the 1950s until the early 1990s. It investigates the conditions under which banned and subversive literature existed in the underground network despite the ever-looming censorship apparatus. It is based on theories drawn from the history of the book, sociology of literature, South African literary histories, and on data from secondary and primary sources such as archival material and interviews with, and testimonies from, readers. This thesis focuses on the roles of readers in alternative circuits, by examining the modalities of sourcing, distributing, reading and sharing of imported and local banned publications. It seeks to demonstrate that readers did read banned books and books likely to be banned, showing creativity in the various strategies used to get these books into the country and to share them amongst the largest number of readers, using texts in various fashions, and actively participating to the South African literary industry and broader socio-political affairs.
Ph.D. University of the Witwatersrand, Faculty of Humanities, 2012
Keywords: African literature; alternative literary networks; banned publications; censorship; history of the book; literature; literary history; reader studies; readership; South Africa